2007
DOI: 10.1002/ijc.22508
|View full text |Cite
|
Sign up to set email alerts
|

OCT‐4, an embryonic stem cell marker, is highly expressed in bladder cancer

Abstract: OCT‐4 (also known as POU5F1) is a key regulator of self‐renewal in embryonic stem cells. Regarding the new cancer stem cell concept, the expression of such genes is potentially correlated with tumorigenesis and can affect some aspects of tumor behavior, such as tumor recurrence or resistance to therapies. Although OCT‐4 has been introduced as a molecular marker for germ cell tumors, little is known about its expression in somatic cancers. Here, we have investigated the potential expression of OCT‐4 in bladder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
176
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(200 citation statements)
references
References 23 publications
20
176
1
3
Order By: Relevance
“…It may also be interpreted that poorly differentiated ESCC exhibiting basaloid character possibly acquires stem cell property identified by Oct4 expression. Similar to the our observation, other groups also documented higher number of basaloid or poorly differentiated carcinoma cells expressing Oct4 in patients who either had residual or recurrent ESCC (Atlasi et al, 2006;Hu et al, 2008;Chen et al, 2009;Koukourakis et al, 2012). Koukourakis et al (2012) and Islam et al (2014) observed high percentages of Oct4 in recurrent oral, head and neck SCC.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…It may also be interpreted that poorly differentiated ESCC exhibiting basaloid character possibly acquires stem cell property identified by Oct4 expression. Similar to the our observation, other groups also documented higher number of basaloid or poorly differentiated carcinoma cells expressing Oct4 in patients who either had residual or recurrent ESCC (Atlasi et al, 2006;Hu et al, 2008;Chen et al, 2009;Koukourakis et al, 2012). Koukourakis et al (2012) and Islam et al (2014) observed high percentages of Oct4 in recurrent oral, head and neck SCC.…”
Section: Discussionsupporting
confidence: 91%
“…There are two studies (Tai et al, 2005;He et al, 2012) who had reported Oct4 expression by dysplastic and hyperplastic esophageal mucosa confining to the proliferative zone, and not expressed by the normal mucosa. Oct4 positivity is reported in certain adult tissue including benign endometrial stromal cells (Atlasi et al, 2006;Cauffman et al, 2006;Mathai et al, 2006;Katona et al, 2007;Zangrossi et al, 2007;Atlasi et al, 2008;Forte et al, 2009). We observed slightly higher sensitivity by PCR technique than by the conventional immunohistochemistry method in detecting Oct4 expression, which is similar to other reported data (Atlasi et al, 2006;Xi et al, 2011;.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…POU5F1 reactivation has been found to be implicated in human tumours; aberrant POU5F1 expression was detected in germ cell tumours [36,37] and recently in bladder cancer [38]. Furthermore, ectopic Pou5f1 expression in adult mice resulted in dysplastic growth of epithelial tissues [39].…”
Section: Discussionmentioning
confidence: 99%